Analysis of The Application Of Work Motivation In The House Security Unit Of Bank Indonesia PT. Jakarta Profitry Fund Trans - Yusuf, Solehuddin; Hulasoh, Ela (Implikasi: Jurnal Manajemen Sumber Daya Manusia, 2024)
This research aims to analyze and explain the work motivation of the Bank Indonesia home security unit at PT. Trans Dana Profitri Jakarta. This research is a type of qualitative descriptive research with data collection techniques used through interviews, documentation, and field observations, literature studies. The data sources for this research are primary and secondary data sources. The data analysis method for this research is in stages 1) data reduction, 2) data presentation, and 3) drawing conclusions. The results of the research show that motivation for security units in the Bank Indonesia office environment must be intensively carried out by leaders in the field and also the company must continue to monitor the performance of leaders in the field. The results of the survey that was carried out found findings regarding several things or indications that caused a decrease in the work motivation of security forces in the field. Some of the factors found in the field include 1. The absence of a career path, 2. Leave rights that cannot be taken, 3. The contract work system which is always looming which can be terminated at any time by the company if there is the slightest problem. 4. There is an impact other things, such as the existence of a new policy regarding the corona virus outbreak, PT Trans Dana Profitri Jakarta can make efforts to provide policy information in the field so that security unit personnel can accept the policy gracefully and also the leadership can provide solutions to current problems. faced in the field considering the number of personnel who complained about this. Work motivation such as praise, appreciation, work equipment, work comfort, work ability, and work discipline are felt to be sufficient. The direct motivation given emphasizes direct encouragement such as praise given, such as positive motivation in the form of flattery, awards given according to performance. Meanwhile, indirect motivation itself emphasizes equipment that is suitable for use so that work comfort can be felt in the field.